Professional Tranining Practice Assistance Ship for Students of Islamic Education Management Study Program at Madrasahs - Hasnadi (PT FORMOSA CENDEKIA GLOBAL, 2022)
Professional training practice is one of the student activities to apply the knowledge gained while attending lectures to the world of work and as a place to gain experience about the introduction of employment. Many students experience problems while participating in professional training practice activities, including; less able to adapt to the madrasa environment, students are less active and creative because they often wait for assignments given by tutors, students are focused on the culture of madrasa administrative services, and are less open to accompanying lecturers for discussions. The purpose of this dedication in the form of assistance is to support the smooth implementation of professional training practice activities for students of the Islamic Education Management study program STAIN Teungku Dirundeng Meulaboh. The results of this dedication concluded that mentoring can increase student activity, creativity, ability, motivation and self-confidence so that the activities carried out by students while participating in professional training practices at madrasas are more focused.